Magnetic resonance imaging - Velan, Sendhil (Henry Stewart Talks, 2010)
History of magnetic resonance, Magnetic resonance scanners, Nuclei in a magnetic field -Excitation, Chemical shifts, T1 relaxation, T2 relaxation, Spin echo, Gradient echo and its imaging sequence, Slice selection/thickness, Phase and frequency encoding of the MR signal, Spatial resolution, K space, Image contrast and noise, T1 contrast: TR and flip angle, T2 contrast, Signal to noise and contrast to noise in MRI, Localized spectroscopy, Volume localized MRS sequence, Volume localization using PRESS, STEAM, Brain MRS, Spectroscopic imaging
Reviewed at 2022/04/12